The Effect of Internal Control, Accounting Professional Ethics and Compensation on Fraud Risk with UN Ethical Behavior as Intervening Variables - Ajeng Wijayanti; Dede Sunaiah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Fraud that occurs in a company requires important attention in overcoming it so that a company is able to minimize the occurrence of fraud. It is necessary to know the influence factors of the occurrence of fraud so that it can be used as a reference for companies in developing company management, especially in the financial sector. This study was conducted with the aim of knowing the effect of internal control, professional ethics of accountants and the suitability of compensation to the risk of fraud which is strengthened by the presence of unethical behavior in employees. This study uses a quantitative approach with a correlational research design. Data was collected by distributing questionnaires. The data analysis technique in this research is using the SPSS application 21 version and using regression analysis test to answer the hypothesis that has been made. The results showed that the variables of internal control, accounting profession ethics, compensation suitability and unethical behavior had a significant influence on the risk of fraud. This is reinforced by the existence of unethical behavior variables that are able to strengthen the relationship between internal control and the suitability of compensation for the risk of fraud, but unethical behavior has not been stated to be able to strengthen the relationship between the influence of the ethics of the accounting profession on the risk of fraud.